Sosialisasi Intensifikasi Budidaya Magot (Black Soldier Fly) sebagai Upaya Mendukung Kemandirian Pakan Akuakultur di Desa Sukoharjo, Wonosobo - Lilik Setiyaningsih; Frentina Murti Sujadi; Purnama Sukardi; Irfan Hanifa; Hanisya Putri Kania Mardika; Anandita Ekasanti; Baruna Kusuma; Hamdan Syakuri; Asro Nurhabib; Jefri Anjaini; Aufa Dzaki; Tania Yuliana; Yohanes Harvinda; Hana (Universitas Mataram, 2026)
The high cost of commercial feed is a major constraint on aquaculture development because it accounts for a substantial proportion of total production costs. BUMDes Hardjo Utomo in Sukoharjo Village, Wonosobo Regency, has developed Black Soldier Fly (Hermetia illucens) larvae, commonly known as maggots, as a locally available and environmentally sustainable alternative feed ingredient. However, its development is constrained by limited cultivation infrastructure, inadequate sanitation, low production efficiency, and insufficient technical knowledge among community members. This community service program aimed to improve the knowledge and understanding of BUMDes managers, fish farmers, and local residents regarding intensive BSF larvae cultivation to support aquaculture feed self-sufficiency. The program was implemented through educational presentations, interactive discussions, question-and-answer sessions, and brief interviews. The materials covered the BSF life cycle, selection and management of organic waste, preparation of cultivation media, moisture control, sanitation, harvesting techniques, and the utilization of BSF larvae as an alternative protein source for fish feed. The participants showed high enthusiasm and actively discussed practical problems, including low larval productivity, unpleasant odors, contamination by inorganic waste, and difficulties in maintaining cultivation media quality. The post-activity evaluation indicated that the participants gained a better understanding of hygienic cultivation practices, organic waste separation, environmental management, and efficient harvesting methods. The activity also increased community awareness of the economic and environmental benefits of BSF cultivation as part of a circular economy system. In conclusion, the program improved community knowledge and motivation to implement more intensive and sustainable BSF larvae cultivation, thereby supporting local aquaculture feed self-sufficiency and environmentally responsible organic waste management in Sukoharjo Village.